Development of a Complex Thinking Test Instrument for Decision Making of Environmental Change Topics - Yuniarti, Anisyah; Afandi, Afandi; Triyanti, Asih; Artika, Wiwit (Jurnal Pendidikan MIPA, 2024)
The development of test instruments to measure students' decision-making abilities is rarely used in learning. This research aims to develop a complex thinking test instrument for decision-making aspects of environmental change topics. This type of research is research and development (R&D) using a 4-D model modified to 3-D (definition, design, and development) and combined with test instrument development using six stages. Interviews, test instrument validation sheets, and tests were conducted during research data collection. The test instrument developed consisted of 12 descriptive questions and was tested on 363 high school students. Data analysis consisted of content validity, inter-rater reliability, and Rasch analysis. Before the test instrument was tested, it was validated by seven experts. The research results show that the content validity analysis developed is valid because of V-count =0.94 > (V-table =0.76). Interrater reliability analysis obtained a value of 0.806, categorized as good. Item validity (item fit) shows 12 valid questions. The difficulty level of the questions (item measure) shows that three questions are challenging, three are complicated, four are easy, and two are straightforward. Reliability shows an excellent Cronbach's alpha value (0.89), a reasonable person reliability value (0.85), and an excellent item reliability value (0.98). Based on the analysis results, it can be concluded that the questions are declared valid and reliable.       Keywords: development, test instrument, decision making, presseisen taxonomy, rasch analysis.DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1893-1905